Pitfalls in diagnosis and management of carbon monoxide poisoning. Issue 1 (January 1996) - Roy, B; Crawford, R
Abstract : Five members of one family suffering from carbon monoxide poisoning are described. Three were initially diagnosed as food poisoning cases at another hospital. A high level of suspicion is required to ensure early diagnosis. Indications for hyperbaric oxygen include: loss of consciousness, neurological signs and symptoms other than mild headache, cardiac complications, carboxyhaemoglobin > 40%, and pregnancy.